Inspiring and Encouraging Organisational Knowledge Sharing Through Religion - Ramlee Abdul Rahman; Basri Hassan, (Universiti Sains Islam Malaysia, 2024)
Presenter from Maritime Institute of Malaysia (MIMA)and International Islamic University Malaysia (IIUM)